2017
DOI: 10.3847/1538-4357/aa7dd9
|View full text |Cite
|
Sign up to set email alerts
|

Local Stability and Global Instability in Iron-opaque Disks

Abstract: The thermal stability of accretion disk and the possibility to see a limit-cycle behaviour strongly depends on the ability of the disk plasma to cool down. Various processes connected with radiation-matter interaction appearing in hot accretion disk plasma contribute to opacity. For the case of geometrically thin and optically thick accretion disk, we can estimate the influence of several different components of function κ, given by the Roseland mean. In the case of high temperatures (∼ 10 7 ) K, the electron … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Second, the opacity drives convection that isn't present in the previous simulations, which enhances the nonradiative fluxes carried in the simulations. However, the dependence of shearing box simulations on box size, combined with timedependent global modeling (Grzȩdzielski, Janiuk & Czerny 2017) strongly motivates further study of UV opacity effects in global numerical simulations.…”
Section: Thermal Instability In Radiation Pressure Dominated Accretionmentioning
confidence: 99%
“…Second, the opacity drives convection that isn't present in the previous simulations, which enhances the nonradiative fluxes carried in the simulations. However, the dependence of shearing box simulations on box size, combined with timedependent global modeling (Grzȩdzielski, Janiuk & Czerny 2017) strongly motivates further study of UV opacity effects in global numerical simulations.…”
Section: Thermal Instability In Radiation Pressure Dominated Accretionmentioning
confidence: 99%
“…We compute the opacity value self-consistently with the density and temperature at each radius with an iterative process, using as reference stellar opacity tables (at solar metallicity) from the Opacity Project (Seaton et al 1994;Seaton 1995). This is important since the density and temperature regimes relevant for AGN disks imply opacities that can be significantly different from the electron scattering value (e.g., see Jiang et al 2016;Czerny et al 2016;Grzȩdzielski et al 2017a). Further, we assume a downward component of the X-ray emission (η) and a disk albedo (a disk ), which modify the disk equations from the usual (1 − f ) factor (M03; Svensson & Zdziarski 1994) to:…”
Section: The Disk-corona Modelmentioning
confidence: 99%
“…Our global simulations, with a range of µ-paramater values for the stress tensor, have shown that the limit cycle oscillations appear. They are suffering some disturbances from the Iron Opacity Bump, but nevertheless are still expected in AGN over a wide range of black hole mass [19].…”
Section: Modified Stress Tensormentioning
confidence: 99%